Reliability Analysis a Two-Unit Cold Redundant System Working in a Pharmaceutical Agency with Preventive Maintenance. Issue 1 (May 2021) - Malhotra, Reetu; Dureja, Tanishq; Goyal, Aashish
Abstract: The present paper examines the working and reliability of a pair of a two-unit cold redundant system in a pharmaceutical agency. Initially, out of two units, one unit is operative and the other unit acts as a cold redundant. On the failure of the working unit, the redundant unit is put to work. As the demand varies, the manufacturing of the product is also very much affected and so the machines may need to put into the rest period when the vast range of manufacturing is in the distinction to those demanded. It leads to a decline in the warranty period of the product. Additionally, another factor of the preventive/corrective maintenance (PM/CM) is also taken into the consideration. The main aim is to an evaluation of the expected rest period and expected PM/CM period and to determine the maximum profit gained by the company using the Markov process and regenerative technique. The authors have calculated various measures of the system's effectiveness. Numerical consequences and graphs of a precise case are additionally included.